Hedge Fund Activism on Dual Edges: A Comprehensive Study - Zhang, Chenqing; Li, Siqi (Transactions on Economics, Business and Management Research, 2024)
This comprehensive study explores hedge fund activism (HFA), its impact on corporate governance, and shareholder value. It outlines the operational mechanisms of HFA, including target selection, share acquisition, influence exertion, and pushing for change. The study also delves into HFA's aggressive investment strategies, contrasting them with traditional funds. It examines HFA's positive impacts, such as improved corporate governance and shareholder value, and negative consequences, like short-termism and increased market volatility. The paper further analyzes HFA through an ESG lens, highlighting its potential to disrupt CSR practices and affect employee health. Case studies of Yahoo and J.C. Penney illustrate both the successes and failures of HFA. The study concludes by suggesting areas for future research and action, emphasizing the need for a balanced approach to harness HFA's benefits while mitigating its risks.